THE ANALYSIS OF THE INFLUENCE OF NON-TARIFF BARRIERS ON BOSNIA AND HERZEGOVINA TRADE WITHIN CEFTA 2006 - Senija Nuhanović; Mirnesa Baraković Burikić (Economic Review)
The ultimate goal of most European countries, especially of the Western Balkan countries, is to become full members of the European Union (EU). The mentioned countries are included in the Stabilisation and Association Process (with the Stabilisation and Association Agreement (SAA) as its main segment) and they are in a different stage of EU accession. Cooperation among the Western Balkan countries within the Central European Free Trade – CEFTA 2006, is the starting point for their future cooperation with the EU member states, allowing them to prepare for joining the common EU market more quickly and efficiently. By signing the Central European Free Trade Agreement (CEFTA 2006), Bosnia and Herzegovina (BiH) became a member of a free trade zone, together with other (non-EU) Western Balkan countries and Moldova. Removing trade barriers and improving trade cooperation was the primary goal of signing this agreement. Although the tariffs in the trade among inter-CEFTA countries were abolished, the existence of a large number of non-tariff barriers is evident, which significantly hampers most economic and trade relations in particular, within the mentioned regional group. Therefore, the starting point in this work is to study the impact of non-tariff barriers on the size of BiH import/export within CEFTA 2006. This paper presents the research results obtained on the basis of processing the secondary data sources using quantitative and qualitative methods. To check the main and supporting hypotheses we used the Spearman's correlation coefficient. Based on the analysis, it was found that there is a significant correlation between the non-tariff barriers and BiH import/export during this period.